Effect of enzymes and clarifying agents on quality parameters of elderberry juice - Szalóki-Dorkó, Lilla; Nagy, Eszter; Stéger-Máté, Mónika (Acta Biologica Szegediensis, 2016)
Natural food colorants are usually used in concentrated form. Production of concentrate including enzymes, temperature, clarifying agents and mechanical operation may have significant influence on valuable components of the end product. In our study, we investigated the effects of two different pectolytic enzyme preparations (Fructozym P and Pectinex BE XXL) and five clarifying agents (three bentonites and two silica sols) on total polyphenol, total anthocyanin content and colour parameters of Haschberg and Samocco elderberry juices. Our results showed that enzymes and clarifying agents applied during juice production influenced the investigated quality parameters of both varieties. Generally, in case of Samocco variety Fructozym P with bentonites, while in case of Haschberg Pectinex BE XXL with silica sols proved the most effective combinations to reach high quality values. This fact should be considered in case of industrial application.